2001
DOI: 10.1177/135945750101500107
|View full text |Cite
|
Sign up to set email alerts
|

‘Mummy Can Play Too…’ Short-Term Music Therapy with Mothers and Young Children

Abstract: This article describes two short-term music therapy groups with mothers1 and young children at the Croft Unit for Child and Family Psychiatry. As there is very little documented music therapy work with this client group, the authors examine literature that describes other therapeutic interventions and that looks at the links between mothers and young children's behaviour. This literature review suggests that early intervention with parents who are experiencing difficulties with their children is both important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Researchers have conducted family-based music therapy studies in a music therapy clinic (Smeijsters & Storm, 1996), a substance abuse treatment facility (Loveszy, 2006), a family-based treatment center (Oldfield & Bunce, 2001;Oldfield, Bunce, & Adams, 2003), and a community setting (Walworth, 2009). In one study, data collection expanded to multiple community settings (Nicholson, Berthelsen, Abad, Williams, & Bradley, 2008).…”
Section: Downloaded By [University Of Nebraska Lincoln] At 13:30 11 mentioning
confidence: 99%
“…Researchers have conducted family-based music therapy studies in a music therapy clinic (Smeijsters & Storm, 1996), a substance abuse treatment facility (Loveszy, 2006), a family-based treatment center (Oldfield & Bunce, 2001;Oldfield, Bunce, & Adams, 2003), and a community setting (Walworth, 2009). In one study, data collection expanded to multiple community settings (Nicholson, Berthelsen, Abad, Williams, & Bradley, 2008).…”
Section: Downloaded By [University Of Nebraska Lincoln] At 13:30 11 mentioning
confidence: 99%
“…Much of the literature focuses on mothers, particularly adult mothers. Cumulatively, research findings suggest that parent-child music programs can: 1) encourage engagement and bonding (Edwards, 2011;Lyons, 2000;Nicholson, Berthelsen, Abad, Williams, & Bradley, 2008;Oldfield, Adams, & Bunce, 2003;Oldfield & Bunce, 2001); 2) model parenting skills through children's music and movement activities (Burrell, 2011;Creighton, 2011;Kelly, 2011); 3) nurture parent-child interactions (Edwards, 2011;McDonald et al, 2009); 4) stimulate child developmental and social skills (Kelly, 2011;Nicholson, Berthelsen, Abad, Williams, & Bradley, 2008); and 5) support maternal wellbeing (Gudmundsdottir & Gudmundsdottir, 2010). Moreover, parent-child music programs have been well received by families from disadvantaged and marginalized circumstances (Cunningham, 2011;Kelly, 2011;Ledger, 2011;Nicholson et al, 2008).…”
Section: Parent-child Music Groupsmentioning
confidence: 99%
“…Abad and Edwards (2004) reported the start up of the Sing & Grow programme in Australia and proposed that 'the use of music therapy to assist parents to extend their repertory of successful and nurturing parental behaviours in interaction with their young children' was 'relatively new' (Abad and Edwards 2004 p. 14), and 'under reported and researched' (p. 5). Oldfield and Bunce (2001) had also described that music therapy work with mothers and young children was unusual. Family-centred music therapy had been provided in a playgroup programme with early intervention goals some years earlier in Australia (Shoemark 1996).…”
Section: Parent-infant Music Therapymentioning
confidence: 99%
“…A report of a music therapy group programme with self-referred 'well' families reported benefits with offering social support and additional ways to deal with parental challenges (Mackenzie and Hamlet 2005). Other music therapy programmes with mothers and their infants have shown benefits in the quality of interaction observed, and self reported satisfaction with participation in the sessions (Oldfield and Bunce 2001;Oldfield et al 2003). Observations in music therapy sessions with mothers and their infants from the asylum seeker community in Limerick, Ireland showed that interactions and interpersonal engagement improved for these vulnerable, 'preoccupied' mothers and their children .…”
Section: )mentioning
confidence: 99%